Competence-Based Approach: Tools for Self-Management of the Youth Worker - Toncheva–Zlatkova, Violeta (UNWE Yearbook, 2021)
The purpose of this article is to introduce the competence-based model for youth workers and to link it to diversity of personal youth work practices. The first part is devoted to the youth work and a wide range of activities, topics and measures provided by a number of actors in assorted fields and settings. It also discusses the roles of youth workers and proposes different tools for their self-management. The second part of the text is devoted to the competence-based approach (content, origins and intentions) and its applicability in the context of youth work. It puts the European Training Strategy (ETS) competence model for youth workers within the context of European youth policies and programmes and explains the benefits and challenges in front of youth workers. It also discusses how this model can support training and provoke professional development.